Agrolandscape structure and damage caused by red squirrels to cocoa pods - Molina, Misael; Mazón, Marina (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
Cocoa is a strategic resource because it hosts high biodiversity, and it is a reliable source of foreign exchange. In Venezuela, fungi and red squirrels mainly affect its productivity. The objective was to evaluate the influence of the cocoa crop structure on the level of damage caused by red squirrels on the pods. The vegetation structure was defined in 15 farms assessing the cocoa tree biomass, the magnitude of shade tree cover, number of associated crops, presence of alternative fruit trees, and the type of ecological succession present in the surrounding. The % of damage was calculated, and nonparametric tests were used to process data. The damage was higher in crops with less shade cover, a more abundant number of associated crops, and alternative fruit trees. Squirrels used the cocoa pods opportunistically but preferred other fruits. It is concluded that pods can be a complementary food for squirrels to the extent that the cocoa plantation is more complex and has a connection with the forest. Shade cover did not directly influenced squirrels, but it is crucial for bird predators which are more sensitive to disturbance.